Generative Learning Model in Mathematics: A Solution to Improve Problem Solving and Creative Thinking Skill - Kusairi, Kusairi; Syaiful, Syaiful; Haryanto, Haryanto (Indonesian Journal of Science and Mathematics Education, 2020)
The purpose of this study is to determine the effect of Generative learning model on mathematical problem-solving and mathematical creative thinking skills. The method used in this research is Quasi-Experiment method with post-test only design. The sample in this study was 75 fifth grade students at SDIT Al-Azhar Jambi taken by random sampling technique. Data collection techniques using essay tests of mathematical problem-solving and mathematical creative thinking skills. Data analysis was done by normality test, homogeneity and hypothesis testing using one-way ANOVA by SPSS software 25.0. The results of data analysis show that there is an effect of Generative learning model on mathematical problem solving and mathematical creative thinking skills, and the application of Generative learning model with student worksheet are better than just Generative learning model or conventional learning model.